2010
DOI: 10.1007/s12262-010-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Trauma of facial skeleton in children: An indian perspective

Abstract: Mandible is the commonest facial bone fracture in children, more often caused by accidental fall from height. The high osteogenic potential of pediatric mandible allows non-surgical management to be successful in an increased proportion of younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
15
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 15 publications
13
15
1
1
Order By: Relevance
“…In similar series, Holland et al [8] reported that 3 % of children presenting to the emergency department with facial trauma, had a 2:1 male to female ratio. This was in accordance with earlier studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In similar series, Holland et al [8] reported that 3 % of children presenting to the emergency department with facial trauma, had a 2:1 male to female ratio. This was in accordance with earlier studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
“…This finding was similar to previous studies [1,2,7,9,12], however Holland et al [8], Posnik et al [14] and Bamjee et al [15] reported that road traffic accident is the most common cause. Gassner et al [1] reported that majority of accidents occurred during playing (58.2 %) followed by sporting activities (31.8 %), traffic accidents (5 %), assaults (3.9 %).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations